RADAR ABSORBING MATERIALS BASED ON TITANIUM THIN FILM OBTAINED BY SPUTTERING TECHNIQUE. DOI: 10.5028/jatm.2011.03030511 - Viviane Lilian Soethe; Evandro Luis Nohara; Luis Cesar Fontana; Mirabel Cerqueira Rezende (Journal of Aerospace Technology and Management, 2012)
Titanium thin films with nanometer thicknesses were deposited on polyethylene terephthalate (PET) substrate using the triode magnetron sputtering technique. It was observed that the titanium thin film-polymeric substrate set attenuates the energy of the incident electromagnetic wave in the frequency range of 8 to 12 GHz. This result allows to consider this set as a radar absorbing material, which may be employed in automobile, telecommunication, aerospace, medical, and electroelectronic areas. Results of the reflectivity show that the attenuation depends on the thin film thickness, as a determining factor. Thin films with 25 to 100 nm thickness values show attenuation of the electromagnetic wave energy from around 20 to 50%. Analyses by Rutherford backscattering spectrometry provided information about the thickness of the thin films studied. Hall effect analyses contributed to better understand the influence of the thin film thickness on the electron mobility and consequently on absorption properties.